Nurturing social entrepreneurship knowledge through experience: an action research - Anis Amira AB Rahman; Shah Iskandar Fahmie Ramlee; Rosliza Che Rahim (2015)
This paper aims to reveal the practises of social entrepreneurship pedagogy that based on experiential learning. Social entrepreneurship is an important concept that should be understood and learn. The knowledge of social entrepreneurship should be conversed smoothly and effectively to the tertiary education students. Those students should be able to differentiate the concept and process between social entrepreneurship and commercial entrepreneurship. However, the common practise in tertiary education employed the traditional approach and worse still the didactic approach which will not help the students to reveal their self-learning and creativity. Therefore, this study shares the best practises of social entrepreneurship pedagogy that utilised experiential learning and monitor the progress through action research. The action research in this study employed three main steps which are the planning, the action and observation, and the reflection stage for the first round. In the second round, the same process happened which are re-planning stage, action and observation, and lastly reflection stage. Three main themes have been found which are the knowledge absorption, the application and the appreciation of social entrepreneurship concept. The knowledge easily absorb through mind mapping on the wall. The understanding increase through application of creating and managing social enterprise. Lastly, the knowledge installed in unconscious mind when the social entrepreneurship is appreciated. This study shows that the experiential learning approach is suitable and effective in teaching and learning the social entrepreneurship course. Future research can employed this method and pedagogy in teaching other entrepreneurship courses.